Implementasi Nilai-Nilai Pendidikan Islam dalam Budaya Nemui Nyimah di Masyarakat Lampung Pepadun - Sada, Heru Juabdin; Firdaos, Rijal; Sari, Yunita (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
This study aims to explain how the values of Islamic education in the culture are found in the community of Lampung Pepadun. The implementation of the culture of Nemui Nyimah in the community of Tiyuh Panaragan is seen in hospitality activities, such as there are procedures or adab-adab visiting and receiving guests. Data analysis techniques used by researchers are data reduction, data display, and conclusion drawing / verification. The results of this study state that: The implementation of the culture of Nemu Nyimah in the Tiyuh Panaragan community can be seen in hospitality activities, such as adab-adab visiting and receiving guests in the community of Tiyuh Panaragan. Based on the results of the Nemu Nyimah Study, it is an explicit culture which means that it cannot be seen in any form, but the culture of Nemu Nyimah is always in any activity or event such as deliberation, forum mulei menganai, yasinan, ngakuk majeu (taking girls), and manjau debingei.